Analisis Manajemen Strategi dalam Menghadapi Persaingan Bisnis (Studi Kasus UMKM Dapoer Ibu Hayra) - Devitasari, Citra; Defrizal, Defrizal (Jurnal EMT KITA, 2025)
This study aims to analyze the strategic management applied by UMKM Dapoer Ibu Hayra in facing increasingly fierce business competition, as well as the formulation and selection of business competition strategies. This type of research uses a qualitative method with a descriptive approach. The data collection techniques used are interviews, observation and documentation to 3 informants, namely the owner, admin, and production department. By using the marketing mix concept from McCarthy, it results in UMKM Dapoer Ibu Hayra implementing an effective marketing mix strategy, including quality products with halal certification, competitive prices, diversification of distribution channels, and active promotion both online and offline. In analyzing business competition using Porter's five forces concept, UMKM Dapoer Ibu Hayra focuses on product innovation, service improvement, and effective digital marketing strategies. These strategies have successfully helped UMKM Dapoer Ibu Hayra overcome the threat of new entrants and maintain market share. This research provides insight into how UMKM Dapoer Ibu Hayra can utilize digital technology in marketing strategies, improve distribution efficiency, and strengthen customer relationships.